Tinjauan Hukum dalam Pelaksanaan Pengawasan Sumber Daya Perikanan - Clara Tiwow (Universitas Bandar Lampung (UBL), 2012)
Illegal, unregulated and unreported (IUU) fishing is occurring is not just done by foreign fishermen but also by Indonesia. One cause is the law itself or the application of laws and regulations are complex and burdensome in terms of financing of fishermen. There are two regulation which ordered to have permission of the ship in fisheries, namely Act No. 17/2008 about the Vayoge and Act No. 45/2009 about the change of Act No. 31/2004 about Fishing. Both the legislation speaks of a physical measurement and the health of fish in fishing boats are “overlap” or at least twice in the same checking of an object and grant the same permissions as well. The Act No. 17/2008 on the legal status of the ship can be seen in article 154 up to article 163. Therefore it would manufacture of laws and regulations have to be integrated.